Correlation of Radiological Category with Lung Pathology in Coal-workers' Pneumoconiosis. Issue 3 (July 1962) - Caplan, Anthony
Abstract : The relation between the macroscopic pathology of the lungs of coal-workers and the radiological category of pneumoconiosis on a chest film taken not more than two years before death has been investigated in 238 coal-miners in South Wales. Large lung sections were shown to provide more accurate and convenient material than wet lungs for this comparison and were used to assess the number and character of dust foci and the degree of emphysema. The profusion of dust foci was classified into four grades—very sparse, sparse, moderate, and numerous—using standard lung sections. Emphysema was graded slight, moderate, and severe. The chest radiographs were categorized according to the I.L.O. Classification, 1953. The comparison shows that there is a fairly good correlation between the radiological category and the number and character of dust foci in the lungs at necropsy. The higher the radiological category the greater the likelihood that the lungs will show a large number of dust foci and particularly a higher proportion of fibrotic nodules, and vice versa. Only about 10% of the films read as category 1 showed sparse fibrotic nodules on the lung section, and none showed more than this. Fibrotic nodules occurred more frequently when early complicated pneumoconiosis (category A) was also present. There was no evidence that emphysema was obscuring the recognition of the severity of simple pneumoconiosis on the radiograph. The commonest cause of localized areas of consolidation detected radiologically was progressive massive fibrosis; less commonly, apical scars. Other causes were lung cancer, bronchiectasis, and interstitial fibrosis.